History of the Development of Orientalism: Its Influence on the Modern Islamic World - Mudzakkir, Ahmad; Syamsudduha, Syamsudduha; Half, Abu; Suarni, Suarni (Journal of Indonesian Islamic Studies, 2024)
Orientalism is basically a Western perspective on the East that is often colored by bias and stereotypes. This study aims to analyze the development of orientalism in three main phases: the early phase, the colonial phase, and the modern phase, and its impact on the Islamic world. The method used in this study is a literature review with a qualitative-descriptive approach to explore changes in the orientalism paradigm from time to time. The results of the study show that orientalism, since its inception until today, has played an important role in shaping the global narrative about Islam and the Eastern world. The colonial phase shows how orientalism was used to support the dominance of Western power, while in the modern phase, orientalism is present in the form of new discourses through the media and global politics. This study provides a critical understanding of how orientalism has transformed and remains relevant in the relationship between the West and Islam in the contemporary era.